Language as a Repository of Indigenous Agricultural Knowledge: Insights from the Traditional Minangkabau Agricultural Lexicon - Rina Marnita; Novizar Nazir (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This review paper examines the critical role of language as a repository for indigenous agricultural knowledge, with specific focus on the traditional Minangkabau agricultural lexicon of West Sumatra, Indonesia. Drawing upon interdisciplinary perspectives from ethnolinguistics, ethnobotany, and cultural anthropology, this study synthesizes existing literature to demonstrate how agricultural terminology encodes generations of ecological wisdom, sustainable farming practices, and cultural values. The Minangkabau people, renowned for their matrilineal social system and strong cultural traditions, have developed a rich vocabulary related to rice cultivation, agroforestry, and land management that represents an invaluable repository of traditional ecological knowledge. This review identifies the structural characteristics of the agricultural lexicon, examines its role in transmitting indigenous knowledge across generations, and discusses the threats posed by modernization and language shift. The findings underscore the urgent need for documentation and revitalization efforts to preserve this linguistic heritage as a foundation for sustainable agricultural development and biocultural diversity conservation. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 4: Quality EducationSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land